2009
DOI: 10.1016/j.apcata.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of actual groundwater polluted with nitrate by the catalytic reduction over copper–palladium supported on active carbon

Abstract: Catalytic reduction of nitrate (NO 3 -) in groundwater over a Cu-Pd catalyst supported on active carbon was investigated in a gas-liquid co-current flow system at 298 K. Although CuPd/active carbon, in which the Cu/Pd molar ratio was more than 0.66, showed high activity, high selectivity for the formation of N 2 and N 2 O (98%), and high durability for the reduction of 100 ppm NO 3 -in distilled water, the catalytic performance decreased during the reduction of NO 3 -in groundwater. The catalyst also irreversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The observed concentrations were higher than Croatian and European Union standards and therefore this ground water was unsuitable for use as drinking water without appropriate treatment [6][7][8]. Thus, available methods for the efficient treatment of waters polluted with ammonium ions are gaining increased interest [9][10][11]. The biological methods were frequently used for the wastewater treatment, but due to the presence of microorganisms, for the surface and drinking waters, as well as for the ground waters, ion exchange treatment was favourable [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The observed concentrations were higher than Croatian and European Union standards and therefore this ground water was unsuitable for use as drinking water without appropriate treatment [6][7][8]. Thus, available methods for the efficient treatment of waters polluted with ammonium ions are gaining increased interest [9][10][11]. The biological methods were frequently used for the wastewater treatment, but due to the presence of microorganisms, for the surface and drinking waters, as well as for the ground waters, ion exchange treatment was favourable [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies deal with nitrate solutions prepared using deionized water as solvent; however, groundwater contains various cations, anions and organic species, and because of this a decrease in the performance and stability of catalysts is expected when real groundwater is investigated [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…2b, c), which is due to participation of specific functional groups on the adsorbent surface (Mohan and Karthikeyan 1997;Wang et al 2009). The kinetics of the present study revealed that the adsorbent (H. lixii biomass) showed the significant adsorbing capacity of the metals.…”
Section: Scanning Electron Microscopic Studiesmentioning
confidence: 99%